(untitled) (Journal of Oriental Studies, 2018)
The formation of diasporology as an independent science dates back to the end of the 20th century. The most complete reflection was found in the processes of the emergence of the ethnic diaspora, the main features, typologies, functioning in a new living environment, social significance, their place and role in recipient countries and donor countries, etc. However, there were no separate works on the diaspora policy, although the features of South Korea’s activities in foreign countries were covered in many studies. This article explores the diaspora policy of South Korea in Kazakhstan. In connection with the residence of 100,000 Korean diasporas here for more than 80 years, this issue is very relevant in modern Russian science. The author reveals the notion of «diaspora policy», directions of activity of the South Korean government in Kazakhstan. The study of the peculiarities of the South Korean diaspora policy on the basis of comparative historical, descriptive, synchronous-diachronic methods of research actualizes the role of the South Korean diaspora policy in the development of ethnic communities abroad. The author analyzed various types of support for the Korean diaspora in Kazakhstan in the field of education, culture and language, revealed the role of ethnic Koreans in the economic interaction between South Korea and Kazakhstan.